(untitled) (Scientific journal of the Fergana State University, 2025)
The output circuit of the optotransformer device connected to the consumer is high-voltage. This circuit consists of a generator-type photodetectors that generate anomalous voltage and a dielectric consumer consisting of a working mechanism, and a vacuum working chamber specially designed for obtaining high-efficiency photovoltaic, photosensitive polycrystalline thin semiconductor films was used. The VUP-4 system of forevac and diffusion pumps was used. Semiconductor chalcogenide compounds were selected and studied using the thin film technology using the method of heating and evaporating the material in a vacuum. It was determined that the primary block of the optotransformer is protected from the thermal effects of the radiation radiation of natural external lighting, that is, radiation is generated without thermal effects.